2016
DOI: 10.1007/s11255-015-1208-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and determinants of pruritus in pre-dialysis chronic kidney disease patients

Abstract: CKD-P was almost present in one in every five pre-dialysis CKD patients. Interestingly, the prevalence was not affected by the stage of the CKD. For the first time, our results showed a significant association between CKD-P and peripheral eosinophilia and anemia. Besides this, xerosis cutis seems a determinant factor for CKD-P and its severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 24 publications
2
36
2
2
Order By: Relevance
“…This is similar to findings reported by Solak et al and Berger et al (19,20). This implies that pruritus should be assessed and managed in all CKD patients irrespective of age, gender, stage or etiology.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is similar to findings reported by Solak et al and Berger et al (19,20). This implies that pruritus should be assessed and managed in all CKD patients irrespective of age, gender, stage or etiology.…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of pruritus in this study is 42.9% which is higher than 18.9% reported by Solak et al (19). The higher prevalence in our study may be due to the fact that the study subjects consisted of both predialysis CKD and MHD patients unlike those in the study by Solak et al who were only predialysis patients.…”
Section: Discussioncontrasting
confidence: 75%
“…In a cross-sectional study of 402 patients with stage 2-5 CKD, the prevalence of CKDaP was 18.9%. 26 In this study, pruritus was not affected by the stage of CKD. In a cross-sectional study of skin manifestations in 200 Indian CKD and ESRD patients (50 each in stages 3, 4, and 5 CKD and 50 patients with ESRD on dialysis), the prevalence of pruritus was 36%.…”
Section: Ckdmentioning
confidence: 47%
“…Pruritus is one of the most distressing symptoms in chronic kidney disease (CKD) [2] also termed, "CKD associated pruritus" (CKD-P) [3]. Uremic pruritus is extremely common in patients undergoing hemodialysis [4,5]. For example, a recent study of 18,801 hemodialysis patients demonstrated that pruritus affected approximately 42% of all patients, and 15-49% of patients with chronic renal failure.…”
Section: Introductionmentioning
confidence: 99%